The association of grip strength with cardiovascular diseases and all-cause mortality in people with hypertension: Findings from the Prospective Urban Rural Epidemiology China Study - Weida Liu; Darryl P Leong; Bo Hu; Lap AhTse; Sumathy Rangarajan; Yang Wang; Chuangshi Wang; Fanghong Lu; Yindong Li; Salim Yusuf; Lisheng Liu; Wei Li (Elsevier, 2021)
Background: Both hypertension and grip strength (GS) are predictors of mortality and cardiovascular disease (CVD), but whether these risk factors interact to affect CVD and all-cause mortality is unknown. This study sought to investigate the associations of GS with the risk of major CVD incidence, CVD mortality, and all-cause mortality in patients with hypertension. Methods: GS was measured using a Jamar dynamometer (Sammons Preston, Bolingbrook, IL, USA) in participants aged 35-70 years from 12 provinces included in the Prospective Urban Rural Epidemiology China Study. Cox frailty proportional hazards models were used to examine the associations of GS and hypertension and the outcomes of all-cause mortality and CVD incidence/mortality. Results: Among 39,862 participants included in this study, 15,964 reported having hypertension, and 9095 had high GS at baseline. After a median follow-up of 8.9 years (interquartile range, 6.7-9.9 years), 1822 participants developed major CVD, and 1250 deaths occurred (388 as a result of CVD). Compared with normotensive participants with high GS, hypertensive patients with high GS had a higher risk of major CVD incidence (hazard ratio (HR) = 2.39; 95% confidence interval (95%CI): 1.86-3.06; p < 0.001) or CVD mortality (HR = 3.11; 95%CI: 1.59-6.06; p < 0.001) but did not have a significantly increased risk of all-cause mortality (HR = 1.24; 95%CI: 0.92-1.68; p = 0.159). These risks were further increased if hypertensive participants whose GS level was low (major CVD incidence, HR = 3.31, 95%CI: 2.60-4.22, p < 0.001; CVD mortality, HR = 4.99, 95%CI: 2.64-9.43, p < 0.001; and all-cause mortality, HR = 1.93, 95%CI: 1.47-2.53, p < 0.001). Conclusion: The present study demonstrates that low GS is associated with the highest risk of major CVD incidence, CVD mortality, and all-cause mortality among hypertensive patients. High levels of GS appear to mitigate long-term mortality risk among hypertensive patients.